Characterisation of maternal human leukocyte antigen class I antibodies in suspected foetal and neonatal alloimmune thrombocytopenia. Issue 1 (9th November 2016) - Refsum, E.; Mörtberg, A.; Dahl, J.; Meinke, S.; Auvinen, M.‐K.; Westgren, M.; Reilly, M.; Höglund, P.; Wikman, A.
Summary: Objectives: To investigate the specificities and level of HLA class I antibodies in selected cases referred for suspected foetal and neonatal alloimmune thrombocytopenia (FNAIT). Background: FNAIT occurs in 1 : 1–2000 live births, whereas maternal immunisation against human leukocyte antigen (HLA) class I is common. Whether HLA class I antibodies alone can cause FNAIT is debatable. Material and methods: A total of 260 patient samples were referred between 2007 and 2012. Referrals with maternal HLA class I antibodies and no other cause for the neonatal thrombocytopenia were included for analysis (cases, n = 23). HPA‐1a negative mothers were excluded. Control groups were screened positive mothers of healthy neonates (controls, n = 33) and female blood donors (blood donors, n = 19). LABScreen single antigen HLA class I beads was used for antibody analysis. Clinical records were reviewed for cases. Results: All groups had broad antibody reactivity. Cases had more antibodies with high SFI levels compared with the controls (SFI>9999; medians 26, 6 and 0; P < 0·05) and higher overall median HLA‐ABC and HLA‐B SFI ( P < 0·05). Many of the antibodies were reactive with rare alleles. When reviewing the clinical records, several of the cases had other contributing factors to the thrombocytopenia. There was no correlation between foetal platelet count and antibody levels. Conclusion: Mothers of thrombocytopenic neonates had higher levels of HLA class I antibodies compared with control groups of women with healthy children and female blood donors. However, clinical outcome and antibody response correlated poorly in the heterogeneous case group, indicating a multifactorial cause to the thrombocytopenia in the majority of cases.